Momentum Transport in Heterogeneous Forest Canopies - Hawwa Kadum; Ryan Scott; Sarah E. Smith; Marc Calaf; Raúl Bayoán Cal (Boundary-Layer Meteorology, 2025)
This study investigates the impact of spatial heterogeneity on momentum transport within forest canopies through wind tunnel experiments using 1:200 scale forest models. The models, crafted from 10 Pores Per Inch reticulated foam, emulate a leaf area index of 5.3 and include alternating patches and gaps of various sizes. Statistical results of the mean velocity profiles and velocity standard deviations show that the canopies develop a mixing layer. By employing lacunarity analysis to quantify spatial heterogeneity, we establish that the heterogeneity scale effectively represents variations in canopy height. The success of the lacunarity analysis as a metric is particularly noteworthy, providing a robust and practical measure of heterogeneity that can be easily applied in future research. Control volume analysis reveals that horizontal and vertical momentum advection terms rise as canopy heterogeneity increases, emphasizing its critical role in heterogeneous canopies and the possibility of describing this role using the lacunarity scale. The gaps also give rise to pressure terms through the local pressure gradient at each pattern. The study highlights the higher influence of gap size over heterogeneity scale on momentum flux. These insights contribute to improved parameterization of heterogeneous canopies in numerical weather prediction models, aiding in better representation of sub-grid scale processes and enhancing our understanding of canopy-atmosphere interactions.

Boundary-Layer Processes Hindering Contemporary Numerical Weather Prediction Models - Marc Calaf; Nikki Vercauteren; Gabriel G. Katul; Marco G. Giometto; Travis J. Morrison; Fabien Margairaz; Vyacheslav Boyko; Eric R. Pardyjak (Boundary-Layer Meteorology, 2023)

The Heat-Flux Imbalance: The Role of Advection and Dispersive Fluxes on Heat Transport Over Thermally Heterogeneous Terrain - Travis Morrison; Eric R. Pardyjak; Matthias Mauder; Marc Calaf (Boundary-Layer Meteorology, 2022)

Anisotropy of Unstably Stratified Near-Surface Turbulence - Ivana Stiperski; Marcelo Chamecki; Marc Calaf (Boundary-Layer Meteorology, 2021)
Classic Monin–Obukov similarity scaling states that in a stationary, horizontally homogeneous flow, in the absence of subsidence, turbulence is dictated by the balance between shear production and buoyancy production/destruction, whose ratio is characterized by a single universal scaling parameter. An evident breakdown in scaling is observed though, through large scatter in traditional scaling relations for the horizontal velocity variances under unstable stratification, or more generally in complex flow conditions. This breakdown suggests the existence of processes other than local shear and buoyancy that modulate near-surface turbulence. Recent studies on the role of anisotropy in similarity scaling have shown that anisotropy, even if calculated locally, may encode the information about these missing processes. We therefore examine the possible processes that govern the degree of anisotropy in convective conditions. We first use the reduced turbulence-kinetic-energy budget to show that anisotropy in convective conditions cannot be uniquely described by a balance of buoyancy and shear production and dissipation, but that other terms in the budget play an important role. Subsequently, we identify a ratio of local time scales that acts as a proxy for the anisotropic state of convective turbulence. This ratio can be used to formulate a new non-dimensional group. Results show that building on this approach the role of anisotropy in scaling relations over complex terrain can be placed into a more generalized framework.

The Impact of Surface Temperature Heterogeneity on Near-Surface Heat Transport - Travis Morrison; Marc Calaf; Chad W. Higgins; Stephen A. Drake; Alexei Perelet; Eric Pardyjak (Boundary-Layer Meteorology, 2021)

Large-Eddy Simulation of the Atmospheric Boundary Layer - Rob Stoll; Jeremy A. Gibbs; Scott T. Salesky; William Anderson; Marc Calaf (Boundary-Layer Meteorology, 2020)

Surface Thermal Heterogeneities and the Atmospheric Boundary Layer: The Thermal Heterogeneity Parameter - Fabien Margairaz; Eric R. Pardyjak; Marc Calaf (Boundary-Layer Meteorology, 2020)

Surface Thermal Heterogeneities and the Atmospheric Boundary Layer: The Relevance of Dispersive Fluxes - Fabien Margairaz; Eric R. Pardyjak; Marc Calaf (Boundary-Layer Meteorology, 2020)

Large Wind Farms and the Scalar Flux over an Heterogeneously Rough Land Surface - Marc Calaf; Chad Higgins; Marc B. Parlange (Boundary-Layer Meteorology, 2014)